Secure and pervasive communication framework using Named Data Networking for connected healthcare. (May 2022) - Dudeja, Rajan Kumar; Bali, Rasmeet Singh; Aujla, Gagangeet Singh
Abstract: Connected healthcare system is one of the most critical Internet of Things (IoT) applications offering numerous healthcare services. But it requires the next-generation technologies to collude with the IoT standards to provide prompt end-user services. Thus, a data-centric network architecture like, Named Data Network (NDN) can be effective to tackle the concerns related to communication in the connected healthcare. In this article, we propose a Secure and Pervasive Health Care Framework (SecPHCF) that attempts to process healthcare data securely and transmit it using NDN thereby aiding faster healthcare support. The data dissemination model in SecPHCF contains two operating modes, (a) a consumer-based model where the end-user initiates the data communication process and (b) a producer-based model where alert messages indicating critical conditions trigger the transmission. SecPHCF is validated through extensive simulations on different network scenarios by considering evaluation parameters such as throughput, network delay, packet delivery ratio, and computation overheads. Graphical abstract: Highlights: A content name-based and in-network caching mechanisms of NDN are designed for suitability in effective forwarding of healthcare information generated through different IoT sensors. A framework for implementing pervasive healthcare communication is designed by utilizing NDN as a backbone network. A sensor registration and authentication scheme is proposed followed by a data monitoring system. An adaptive producer–consumer mechanism is proposed to handle data based on the severity level of sensed healthcare parameters.